Experiences of mood changes and preferences for management within stepped psychological care from the perspective of spouses of people with aphasia. Issue 2 (1st February 2023) - Iwasaki, Natsumi; Ryan, Brooke; Worrall, Linda; Rose, Miranda; Baker, Caroline
ABSTRACT: Background: Spouses of people with aphasia are at an increased risk of depression and other mood problems. Despite this, there is limited research addressing the experiences and preferences for psychological care of spouses. Aims: To describe, from the perspective of spouses of people with aphasia: (a) the experience of mood changes, depression, and current practice after post-stroke aphasia for themselves and the person with aphasia; and (b) preferences of care within a stepped psychological care framework. Methods: Four spouses of people with aphasia participated in two in-depth, semi-structured interviews each. Eight interviews were transcribed verbatim and analysed using Interpretive Description. Results: Four core themes were identified: (1) Stroke and aphasia results in mood changes for both the spouse and the person with aphasia; (2) Spouses and people with aphasia experience a lack of psychological supports and other services; (3) Relationships with family, friends, health professionals, and the person with aphasia can influence mood in the post-stroke experience; (4) The implementation of stepped psychological care to stroke rehabilitation is important for spouses and people with aphasia. Conclusion: Spouses experienced largely negative impacts of stroke and aphasia on their mood and wellbeing. They held positive views about the need for psychological care and identified various preferences for intervention. Health professionals may consider the preferences of spouses when providing psychological interventions and support.